Exploring early combination strategy in Latin American patients with newly diagnosed type 2 diabetes: a sub-analysis of the VERIFY study - Sérgio Vencio; Juan P. Manosalva; Chantal Mathieu; Pieter Proot; Hernan Yupanqui Lozno; Päivi M. Paldánius (Diabetology & Metabolic Syndrome, 2021)
Abstract Background Patients with type 2 diabetes mellitus (T2DM) from Latin American countries face challenges in access to healthcare, leading to under-diagnosis, under-achievement of glycemic target, and long-term complications. Early diagnosis and treatment initiation are of paramount importance in this population due to the high prevalence of risk factors such as obesity and metabolic syndrome. The VERIFY study in patients with newly diagnosed T2DM (across 34 countries), assessed the normoglycemic durability (5 years), with early combination (EC) therapy approach versus the traditional stepwise approach of initiating treatment with metformin monotherapy (MET). Here we present the results from the VERIFY study for participants from eight countries in Latin America. Methods Newly diagnosed adult patients with T2DM, HbA1c 6.5–7.5% and body-mass index (BMI) of 22–40 kg/m2 were enrolled. The primary endpoint was time to initial treatment failure (TF; HbA1c ≥ 7.0% at two consecutive scheduled visits 13 weeks apart). Time to second TF was evaluated when patients in both groups were receiving and failing on the vildagliptin combination. Safety and tolerability were also assessed for both treatment approaches during the study. Results A total of 537 eligible patients (female, 58.8%) were randomly assigned to receive either EC (n = 266) or MET (n = 271). EC significantly reduced the relative risk of time to initial TF by 47% versus MET [HR (95% CI) 0.53 (0.4, 0.7) p < 0.0001]. Overall, 46.4% versus 66.3% of patients achieved the primary endpoint in the EC and MET groups, with a median [interquartile range (IQR)] time to TF of 59.8 (27.5, not evaluable) and 33.4 (12.2, 60.1) months, respectively. The risk for time to second TF was 31% lower with EC (p < 0.0092). A higher proportion of patients receiving EC maintained durable HbA1c < 7.0%, < 6.5%, and < 6.0%. Both treatment approaches were well tolerated, and only 3.2% of participants discontinued the study due to adverse events. All hypoglycemic events (EC: n = 7 and MET: n = 3) were single, mild episodes and did not lead to study discontinuation. Conclusion Similar to the global population, long-term clinical benefits were achieved more frequently and without tolerability issues with EC versus standard-of-care MET in this Latin American sub-population. This study is registered with ClinicalTrials.gov, NCT01528254.